"n Waardering vir die positiewe! Waarderende betrokkenheid as "n gemeentelike- en pastorale lens - Schoeman, W. J. (HTS teologiese studies, 2011)
An appreciation for the positive! Appreciative engagement as congregational process and congregational- and pastoral lens The traditional approach of only solving what is wrong is challenged by newer perspectives emphasising the meaning of an appreciation for the positive. The possible meaning of this alternative perspective for the development of a relevant positive practical theology was explored in investigating the possible meaning of the methodology of appreciative inquiry. The benefit of this model, for congregational studies and pastoral ministry amongst others, was investigated, described and illustrated with a case study. After a critical evaluation of the methodology of appreciative inquiry, suggestions for the development of a relevant positive practical theology, incorporating an appreciation for the positive in an appreciative engagement were mapped.